Studi Perbandingan Pemikiran Filsafat Hukum Islam Al-Ghazali, Asy-Syatibi, dan Ibnu Khaldun - Wahyuni, Sri (UIN Sunan Kalijaga Yogyakarta, 2022)
The study of Islamic legal philosophy in the modern era has become an essential study along with the development of human needs for legal products in accordance with the context of the times. The focus of this article is to describe the differences in the philosophical thoughts of Islamic law from several figures, namely: al-Ghazali, Ash-Syatibi, and Ibn Khaldun. This article is library research with data sourced from primary books, then analyzed qualitatively using descriptive, analytical, and comparative approaches. The results of this study indicate that each thinker has different views in the discourse of Islamic legal philosophy as the basis for the existence or absence of Islamic law. Al-Ghazali and Ash-Syatibi believe that a law needs to be based on the existence of revelation so that there is no legal legitimacy if there is no text as its foundation. Al-Ghazali and Ash-Syatibi agreed with the existence of maslahah as the goal of enacting a law. Thus, the law determined based on the texts must be following maqashid ash-syari'ah, namely benefit. Meanwhile, Ibn Khaldun emphasized the portion of reason in understanding God's message from the Prophet.